Screening Extract EtOAc Sponge Derived Fungi Against Clinical Staphylococcus aureus to Obtain Sustainable Natural Product. Issue 1 (December 2021) - Lutfiah, R; Juliasih, N L G R; Hendri, J; Setiawan, A
Abstract: The increasing resistance of pathogenic bacteria to various antibiotics worldwide has become a severe problem for medicine and human health. This study aims to determine the antibacterial activity of extract ethyl acetate (EtOAc) produced by sponge-derived fungi as an antibacterial agent. This study obtained nineteen fungal isolates from the marine sponges in Singaraja, Buleleng Bali, Indonesia. The pathogenic bacteria Staphylococcus aureus was obtained from patients at Abdul Moeloek Hospital, Bandar Lampung. The susceptibility test of Staphylococcus aureus was carried out on nine types of commercial antibiotics using the disk diffusion method. The solid-state fermentation (SSF) method on rice media carried the cultivation and co-cultivation of fungi. The bioactivity of the extract was tested against pathogenic bacteria S. aureus . The results of the susceptibility test to antibiotics showed S. aureus resistance to amoxicillin, ciprofloxacin, erythromycin. Showed that extracts A12RF, A05RF, C36RF had inhibitory activity against the growth of S. aureus at a concentration of 0, 5mg/mL. These results indicate that co-cultivation can induce fungi to produce different secondary metabolites. This basic information is essential for further studies related to the production of fungal bioactive compounds through the co-cultivation stage in the SSF process.